Literasi Media Publik untuk Pekerja Media melalui Akademi Media Publik - Masduki Masduki (Universitas Muhammadiyah Surakarta, 2022)
This paper reports a community development project, particulary an initiative to overcome the scarcity of public media advocacies with strong emphasis to the dissemination of public media knowledge. The advocacies to urge public media as a pillar of a democratized media in Indonesia has been going on since 2002. However, most movements are centered solely on academic forums, research or political lobby aspiring policy changes to Indonesian policymakers. This project fills the gab by establishing media academy, a model of public media course targeted public media professionals. This project was organized throughout August and September 2021, involved two institutions: the Communication Study Program of Universitas Islam Indonesia and Public Broadcast Clearing House (RPLPP) as the main partners of this social program. The course provides an interactive online course involving 15 participants and 8 mentors using Zoom meet application. In addition to lectures on public media system and its policies, participants of this course receive assistance in their creation as well as production of a public oriented content which are worthy of being displayed on their digital media channels. This activity succeeded in enriching the participants’ insight and analytical skills on public media issues. It also succeeded in designing a public media curriculum, which could be adopted by higher education institution of communication in Indonesia.